Sensitivity and Effect of Ignition Timing on the Performance of a Spark Ignition Engine: An Experimental and Modeling Study - A. H. Kakaee; M. H. Shojaeefard; J. Zareei (Journal of Combustion)
The performance of a spark ignition engine is investigated under different values of ignition advance. A two-zone burnt/unburned model with the fuel burning rate described by a Wiebe function is used for modeling in-cylinder combustion, and then experiments are carried out to validate the calculated data. By varying the ignition timing, the results of some characteristics such as power, torque, thermal efficiency, pressure, and heat release are obtained and compared. The results show that optimal power and torque are achieved at 31°CA before top dead center, and performance is decreased if this ignition timing is changed. It is also shown that the maximum thermal efficiency is accomplished when peak pressure occurs between 5 and 15°CA after top dead center.